IMPLIMENTASI PEMBELAJARAN BERBASIS BERTANYA PRODUKTIF UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN KEMAMPUAN KOGNITIF SISWA - Kurniawan, Ade; Masjudin, Masjudin (Media Pendidikan Matematika, 2018)
The problems in mathematics learning at MTs NW Linsar are low of studentâ€™s social skills and cognitive abilities. Students are less active in discussing learning. Students are less accustomed to asking questions or given questions. Interactions that occur often one direction from teacher to student. In fact, it becomes a mindset that mathematical people are often identified with people who are unable to communicate, lack socialization, and seem to be absorbed in their own fun. In an effort to overcome these problems researchers implemented mathematical learning based on productive questions. Therefore, the purpose of this study was to improve the social skills and cognitive abilities of students through the implementation of productive mathematics-based learning tools. Productive questioning is a questioning process by giving open, structured, and systematic questions to students to get an understanding of a concept. The type of this research is research is Classroom Action Research (CAR). This research was conducted at NW Lingsar MTs with 27 students. The instrument of this research is the Social Skills observation sheet and student cognitive ability evaluation test sheets. Based on the results of data analysis, in the first cycle the average score of students' social skills was 74.2% with the Good category. The cognitive ability score reaches an average of 73.2% which is in the high category. Furthermore, in the second cycle, the average score of students' social skills reached 89.2% with the Very Good category. The score of cognitive abilities reached an average of 93.3% which was in the very high category. Thus, it can be concluded that the implementation of productive questioning based learning can to improve social skills and student cognitive abilities on subject matter Set at MTs NW Lingsar in academic yearÂ  2017/2018.